HUBUNGAN ANTARA POLA MAKAN IBU HAMIL DENGAN PENAMBAHAN BERAT BADAN DAN KADAR HEMOGLOBIN TRIMESTER II DI PUSKESMAS PAHANDUT KOTA PALANGKA RAYA TAHUN 2018 - Agnes Daniella; Triawanti; Fatmaria (Jurnal Kedokteran Universitas Palangka Raya, 2021)
Healthy eating patterns for pregnant women must meet the needs of pregnant women. Unhealthy eating patterns can make the nutrients received do not meet the needs of pregnant women and cause some effects on pregnant women. Macronutrient nutrition and micronutrient nutrition related to the health of pregnant women must meet the energy needs of + 2500 Kcal during pregnancy. Good nutrition during pregnancy affects the weight gain of pregnant women. Low nutritional status and wrong diet in pregnant women can cause less weight and anemia.Research purposes. Knowing the relationship between healthy eating patterns of pregnant women with weight gain and second trimester hemoglobin levels.The type of research used is analytic observational research. The population of this study were pregnant women in Pahandut Health Center, Palangka Raya City. Using total sampling technique where the samples taken were all II trimester pregnant women who met the inclusion criteria in May-August 2018 totaling 89 people. Data analysis used Chi Square (x²) test with significance level (α = 0.05). The respondent's weight gain was 28 respondents (65.1%) with a good diet and good weight gain, there were no respondents with a good diet with less weight gain, as many as 15 respondents (34.9%) with a diet good and excess weight gain. As many as 2 people (7.7%) with poor diet and good weight gain, 21 people (80.8%) with less diet and less weight gain, as many as 3 people (11.5%) with less eating patterns that have excess weight. As many as 2 people (10.0%) with poor diet and good weight gain, as many as 18 people (90.0%) with a poor diet and there were no respondents with a bad diet with excess weight. As well as the Hb level of respondents, as many as 31 respondents (18.8%) with a good diet that is not anemic, as many as 12 respondents (27.9%) with a good diet that is anemic. As many as 8 people (17.4%) with poorer patterns and poor diet patterns that were not anemic and as many as 38 people (82.6%) with poor & poor eating patterns who experienced anemia. The existence of a relationship between pregnant women diet with weight gain and Hb levels of pregnant women in second trimester.